Synthesis and Ion Exchange Properties of Magnesium Molybdosilicate as Dependent on the Ionic Potential of the Exchanging Ions - Bhushan, B. (Asian Journal of Chemistry, 2010)
Magnesium molybdosilicate was synthesized and its ion exchange properties were investigated towards certain metal ammine complexes namely Cu(II), Zn(II), Cd(II), Ni(II) and Co(II) by a batch equilibration technique as a function of pH, concentration and steric characteristics of the exchanging ions.